POTRET PERUBAHAN PROFITABILITAS 16 BANK UMUM DI BURSA EFEK INDONESIA PADA PERIODE 2011-2016 - Eleonora Puspita Yuana, 13.05.51.0183; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2017)
This study aims to analyzed the effect of organizational culture, work motivation, leadership and work discipline on employee performance. The object of research in this paper is the PT. Banyu Herang Abadi XL Pekalongan. Research method using census, amount to 108 respondents.Data collection using questionnaire (questionnaire) by distributing questionnaires to respondents to obtain information.Data collected using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of the instrument, regression analysis to examine the effect of partially each independent variable tested by regression analysis. The results of the research are: (1) the organizational culture has a positive and significant impact on employee performance. (2) the motivation of work has a positive and significant impact on employee performance.(3) the leadership negative and no significant influence on employee performance. (4) the discipline of work has a positive and significant impact on employee performance. Keywords : Oranizational Culture, Work Motivation, Leadership, Work Discipline, and Employee PerformanceDAFTAR PUSTAKAAlindra, A. I. (2015). Analisis Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Depok Sports Center . Skripsi S1 Universitas Negeri Yogyakarta .Amir, M. F. (2015). Memahami Evaluasi Kinerja Karyawan . Jakarta: Mitra Wacana Media.Amri, K. (2015). Pengaruh Kepemimpinan, Motivasi, Disiplin Kerja, Dan Pelatihan Kerja Terhadap Kinerja Karyawan Bmt Bima Fikri Yogyakarta . Skripsi S1 Universitas Islam Negeri Sunan Kalijaga Yogyakarta .Ariyani, D. K. (2013). Pengaruh Budaya Organisasi, Motivasi, Kepuasan Kerja Terhadap Kinerja Karyawan Pada Pt. Mandalatama Armada Motor Semarang. Management Universitas Dian Nusantoro .Bangun, Wilson, (2012). Manajemen Sumber Daya Manusia. Penerbit Erlangga. Bandung.Ghozali,  I.  2006. Aplikasi  Analisis  Multivariate dengan  Program  SPSS.  Edisi  4.  Semarang: Badan Penerbit Universitas Diponegoro.Hasibuan, Melayu S.P, (2003). Manajemen Sumber Daya Manusia, Edisi Revisi. Bumi Aksara, Jakarta.Latuny, Y. (2013). Pengaruh Budaya Organisasi Dan Motivasi Terhadap Kinerja Karyawan PT Allianz Life Indonesia Di Denpasar. Megister Manajemen Program Pascasarjana Universitas Udayana Bali .Liana, L. (2017). Pengaruh Motivasi dan Komitmen Organisasional pada Kinerja Guru Didimensi oleh Kepuasan Kerja. Prodi Manajemen Fakultas Ekonomi dan Bisnis, Universitas STIKUBANK .Lufitasari, R. (2014). Pengaruh Motivasi Kerja, Disiplin Kerja, dan Kompensasi Terhadap Kinerja Karyawan Pada Dinas Pendapatan, Pengelolaan Keuangan Dan Aset D.I Yogyakarta. Skripsi S1 Universitas Negeri Yogyakarta .Mangkunegara, A. P. (2015). Manajemen Sumber Daya Manusia Perusahaan. Bandung: PT Remaja Rosdakarya.Nimpuno, G. A. (2015). Pengaruh Disiplin Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Ud. Pustaka Pelajar Yogyakarta . Skripsi S1 Universitas Negeri Yogyakarta .Prabasari, I. G. (2013). Pengaruh Motivasi, Disiplin Kerja Dan Komunikasi Terhadap Kinerja Karyawan Pada Pt. Pln (Persero) Distribusi Bali. Fakultas Ekonomi Udayana Bali .Purnama, M. A. (2016). Pengaruh Disiplin Kerja, Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai. Skripsi S1 Universitas Stikubank Semarang .Putra, G. P. (2013). Pengaruh Disiplin Kerja, Gaya Kepemimpinan, Dan Motivasi Terhadap Kinerja Karyawan Pada Hotel Matahari Terbit Bali Tanjung Benoa-Nusa Dua. Fakultas Ekonomi Universitas Udayana Bali .Robbins, S. d. (2007). Perilaku Organisasi. Ahli Bahasa Drs. Benyamin. Jakarta: Salemba Empat.Sugiyono.  2009. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung : Alfabeta.Sunyoto, Danang, (2015). Penelitian Sumber Daya Manusia, CAPS (Center of Academic Publishing Service), Yogyakarta.Utomo, B. P. (2014). Pengaruh Kepemimpinan, Motivasi Kerja, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dan Dosen. STIMIK DUTA BANGSA SURAKARTA .Yani, I. (2017). Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Perusahaan Daerah Air Minum (PDAM) Kota Kendari. Management Universitas Halu Oleo Kendari .Yunianto, A. (2009). Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja dengan Komitmen Organisasional sebagai Mediasi (Studi pada Perangkat Desa Se Kecamatan Batang Kabupaten Batang). Fakultas Ekonomi, Universitas Stikubank .